Tracking the maturity of industry 4.0 - Alcácer, Vítor (2022)
To track industry 4.0 status, readiness models are used to analyze the state of industry 4.0 technologies’ implementation, allowing the quantification and qualification of its readiness level considering different dimensions. Not all companies are adopting these new technologies with the same ease and with the same pace. There are companies unable to blend the industry 4.0 with their business models, leading to a lack of a correct self-assessment on understanding the reached readiness level. Into this purpose, it is important to understand how companies are facing the digital transformation challenges, what is their perception about the enabling technologies towards the industry 4.0, assess the industry 4.0’ readiness so far, and what are their perception of the barriers to the adoption of these technologies. This paper aims to assess the industry 4.0’ readiness level of companies and discuss the perception of companies about the barriers on the adoption of industry 4.0 with the reached readiness level of companies. New barriers are also brought for discussion on academic community. To this end, empirical data was collected on a sample of 15 companies belonging to an important industrial cluster located in Portugal.